The art of emptiness - Sakaida, Kakiemon XIV 1934-2013 (Japan library (Shuppan Bunka Sangyo? Shinko? Zaidan))
"For several hundred years, Japanese porcelain has been highly acclaimed and sought after around the world. Sophisticated porcelain ware has long been produced in the Arita area of Kyushu, and artisans from the Kakiemon family have gained particular renown for their skill in enamels and their artistic designs. Now, for the first time, the techniques and tradition behind the creation of their ceramic works are disclosed through the words of the late Kakiemon XIV. Starting with his childhood memories, he talks about his father and grandfather and what he inherited from them; how the craftsmen work at the kiln; and how materials such as stone, clay, and firewood play a crucial part in creating the works. Most striking of all are the explanations of aka-e overglaze enamels and nigoshide porcelain, the characteristics that make Kakiemon ware so phenomenal. With more than twenty color plates depicting Kakiemon pieces from museums and private collections, this volume provides rare insight into one of the world's most famous kilns." -- Publisher's description